Development of AR-based Mobile Learning Application for Ruminant Anatomy - Koo, Mei Qi; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2022)
The usage of augmented reality technology in education is becoming more common, as the immersion of augmented reality reduces the boredom of learning and improves learning. Anatomy has always been considered difficult for medical students to learn and memorize since there are so many anatomical terms. Also, mobile learning application that implements augmented reality (AR) is limited. Thus, the objective of this project is to design a mobile learning application for ruminant anatomy entitled “Ruminant Anatomy (AR)” using marker-based AR on the Android platform. Another objective of this project is to develop an interactive learning application using marker-based AR and to perform functional testing and user acceptance testing on the developed application to the target user. The users can view, move, resize, and rotate the 3D models and videos of the ruminant in the AR session and learn the anatomical information in the learning module, as well as take a quiz in the quiz module. The methodology utilized in the application development is Multimedia Mobile Content Development (MMCD). The result of the user acceptance test is 80%. This application is expected to provide an interactive way for users to assist in grasping ruminant anatomy quickly and efficiently.